2022
DOI: 10.1186/s10194-022-01532-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion variance in new daily persistent headache and chronic migraine: an arterial spin-labeled MR imaging study

Abstract: Background and purpose New daily persistent headache (NDPH) and chronic migraine (CM) are two different types of headaches that might involve vascular dysregulation. There is still a lack of clarity about altered brain perfusion in NDPH and CM. This study aimed to investigate the cerebral perfusion variances of NDPH and CM using multi-delay pseudo-continuous arterial spin-labeled magnetic resonance imaging (pCASL-MRI). Methods Fifteen patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Some studies suggested that migraine with visual aura exist in altered neurochemical coupling in the occipital cortex [ 19 ]. Our recent study also reported decreased cerebral perfusion, increased regional homogeneity and multiple frequency amplitudes of low-frequency fluctuation in the middle occipital gyrus in patients with NDPH [ 8 , 27 ]. The above evidence suggests that the abnormal functional network and imbalance of neurotransmitters of the occipital lobe might be involved in headache and pain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies suggested that migraine with visual aura exist in altered neurochemical coupling in the occipital cortex [ 19 ]. Our recent study also reported decreased cerebral perfusion, increased regional homogeneity and multiple frequency amplitudes of low-frequency fluctuation in the middle occipital gyrus in patients with NDPH [ 8 , 27 ]. The above evidence suggests that the abnormal functional network and imbalance of neurotransmitters of the occipital lobe might be involved in headache and pain.…”
Section: Discussionmentioning
confidence: 92%
“…4B; p < 0.001) were significantly decreased in the NDPH group compared to the HC group. (8) The FC between the right thalamus and bilateral cuneus (Fig. 5A-C; L: p = 0.015; R: p = 0.025), left calcarine (Fig.…”
Section: Seed-based Fc Between Patients and Hcsmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that 39.28% of NDPH group had photophobia symptoms and their GM volume of calcarine increased. The brain perfusion of occipital in patients with NDPH was altered in our previous study, and we suggested that patients with NDPH may have abnormal activation of the visual system [ 39 , 40 ]. This is not surprising given the visual pathway's established role in nociceptive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study on whether patients with NDPH develop white matter abnormalities or infarct-like lesions on neuroimaging involved 97 patients with NDPH found that only 13 patients with NDPH demonstrated white matter abnormalities, and none had infarct-like lesions [ 30 ]. Our previous arterial spin-labelled magnetic resonance imaging (MRI) study found decreased cerebral blood flow (CBF) and arterial cerebral blood volume (aCBV) values in the right posterior orbital gyrus, right middle occipital gyrus, and ventral anterior nucleus of the right thalamus in patients with NDPH ( n = 15) compared to HCs ( n = 15) [ 31 ]. A cross-sectional voxel-based morphometry (VBM) and surface-based morphometry (SBM) study investigated 23 patients with NDPH and 23 age- and gender-matched healthy controls (HCs) and found no grey matter changes in patients with NDPH [ 32 ].…”
Section: Discussionmentioning
confidence: 99%